FENOMENA PELANGGARAN ETIKA GURU DI MEDIA SOSIAL: TINJAUAN KODE ETIK PROFESI DALAM PERSPEKTIF ISLAM - dzikry_ilahana, anjani; Alyfia Harum Cantika; Much. Febri Ardiynto; Ma'mun Hanif (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Purpose: This study aims to analyze the phenomenon of ethical violations by teachers on social media in the digital era. The research is important because these violations not only damage the image of the teaching profession but also erode public trust in educational institutions and potentially harm students. This study integrates the review of the Teacher Professional Code of Ethics with an Islamic perspective to provide a more comprehensive understanding of the issue. Design/methods/approach: This research employs a qualitative descriptive-analytical approach using multiple case study method. Secondary data were collected through documentation techniques from online news, viral content on social media (Instagram, TikTok, YouTube), and literature related to the PGRI Teacher Code of Ethics and Islamic teachings. Data analysis was conducted using the Miles et al., (2014) model and normative syariah analysis. Findings: The study identified four main patterns of ethical violations: inappropriate flirtatious communication through private chat, sexual harassment in Islamic boarding schools, child grooming, and the decline in students’ respect for teachers that went viral. These cases clearly violate the principles of professionalism in the PGRI Teacher Code of Ethics as well as the Islamic values of amanah (trust), noble morals, and the prohibition of khalwat (seclusion). Research implications/limitations: This research provides important implications for strengthening teachers’ digital ethics, developing guidelines for communication on social media, and integrating Islamic values in teacher professional training. The limitation of this study lies in the use of secondary data, so the interpretation depends on the availability and accuracy of media coverage.